Manajemen Fatigue Post Stroke Secara Non Fisik, Apakah Efektif? - Puspita, Vema Tiyas; Kariasa, I Made (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Stroke is one of the leading causes of death and disability worldwide. One of the complications of stroke isfatigue post stroke (FPS), where the prevalence ranges from 25% -85%. The mechanism of FPS is notestablished yet, it might be caused by physical and mental fatigue. Factors that causes FPS includephysical disability and psychological disorders. Both physical and non-physical interventions have notbeen proven to be effective in treating FPS. The purpose of this study is to explore the effectiveness of nonphysical interventions in overcoming FPS. Literature review was used in this study by searching articlesusing the 3 database, namely Scopus, Ebsco, and Science Direct with the keywords fatigue post stroke, nonphysical intervention, and stroke management. Inclusion criteria are full text journals in English, humanintervention, Randomize Control Trial (RCT) or Quasi experiment research, journals published from 2015-2020 and studies that measure FPS levels as their main objectives. The results of the literature study foundfive RCT articles that fit the inclusion criteria. Three types of intervention were obtained in these articles,there were psychostimulant drugs, Traditional Chinese Medicine (TCM) and psychology intervention.Although not all interventions show significant results, interventions with modafinil, Cognitive BehavioralTherapy and TCM can improve FPS. The results of the literature review can be used as evidence based forfatigue management of stroke patients